Typha latifolia resilience to high metal stress: antioxidant response in plants from mine and flotation tailing ponds - Grdović, Isidor; Kovačević, Milijana; Andrejić, Gordana; Dželetović, Željko; Rakić, Tamara (Archives of Biological Sciences, 2023)
Paper description: Typha latifolia (cattail) inhabits artificial ponds of flotation and mine tailings that are a serious source of environmental pollution by metals. We assessed plant tolerance to specific edaphic conditions, the chemical properties of the substrate, metal concentrations in the plant, and antioxidant enzyme activities. Cattail accumulates metals predominantly in roots. The effects of elevated metal concentrations on the antioxidant enzyme activities depend on the type of enzyme, metal concentrations, and their molar ratios in the plant. Cattail could be a useful component of a biological water treatment system for removing metals from heavily contaminated wastewater, sediments, and technosols. Abstract: Typha latifolia (cattail) forms natural stands in the transition zone of artificial flotation and mine tailings ponds and is contaminated with extremely high concentrations of metals. We assessed the absorption capacity of the plant, metal transfer to leaves, and the effects of elevated metal concentrations on antioxidant enzyme activities. Soil acidity, the pseudo-total and available metal content of the substrate, and metal concentrations in plants were examined. The effects of elevated metal concentrations in plants on antioxidant enzyme activities (superoxide dismutase, catalase, ascorbate peroxidase, guaiacol peroxidase, glutathione reductase) were assessed. Cattails exhibited high metal accumulation levels in roots and a low transfer rate to the leaves. The effects of metal concentrations on antioxidant enzyme activities were found to depend on the type of enzyme, metal concentrations in the plant and their molar ratios, as well as on the pH of the substrate. High activities of antioxidant enzymes indicate increased generation of reactive oxygen species (ROS) and show that metal detoxification mechanisms are insufficient to restrain their toxicity. Pronounced resistance to elevated metal concentrations and high efficiency in metal phytostabilization show that cattail could be a valuable component of biological treatment systems for removing metals from multi-metal and heavily contaminated substrates in the pH range from ultra-acidic to neutral.